PENGARUH FAKTOR KEUANGAN DAN NON KEUANGAN TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Irtanti Retno Astuti; Darsono Darsono (Diponegoro Journal of Accounting, 2012)
This study aims to examine the influence of financial distress, debt default, disclosure, auditor reputation,opinion shopping, and audit lag prior to the granting by the auditor's going concern opinion. Hypothesis (1) Financial distress effect on the provision by the auditor's going concern opinion, (2) Debt default affects the provision of client going concern opinion by the auditor, (3) Disclosure effect on the provision by the auditor's going concern opinion, (4) Auditor’s reputation effect on the provision by the auditor's going concern opinion, (5) Opinion shopping influence on acceptance going-concern audit opinion, (6) Audit Lag influence on acceptance going-concern audit opinion. Population of this research uses 85 manufacturing companies sample listed on Indonesian Stock Exchange (IDX) between 2006 to 2010. Samples obtained by purposive sampling. Data were analyzed with logistic regression analysis. The results showed that audit lag, the auditor's reputation and debt default the previous year affects the provision by the auditor's going concern opinion. Whereas financial distress, disclosure and opinion shopping have no effect on the provision by the auditor's going concern opinion.